The word that moves - H. Welzen (Acta Theologica)
This essay investigates the role of the Bible in spirituality by looking at the relationship between academic exegesis and spiritual reading, mysticism and language, Bible reading as an event in the relationship between God and human beings and liturgy as a mystagogical process.